Incidence, clinical, MRI and investigative features of children with first episode CNS inflammatory demyelination: a prospective British Isles active surveillance study. (24th May 2012) - Absoud, M; Lim, MJ; Chong, WK; DeGoede, C; Foster, K; Gunny, R; Hemingway, C; Jardine, P; Kneen, R; Likeman, M; Nischal, KK; Pike, M; et al.
Abstract : Aims: Childhood central nervous system inflammatory demyelinating diseases (CNS-IDs) are rare disorders presenting to paediatricians but may be the first manifestation of Multiple Sclerosis (MS), a chronic neurological disorder. We aimed to determine the incidence, clinico-epidemiological and neuroradiological features of first episode childhood CNS-ID in the UK and Ireland. Methods: Children under 16 years with events consistent with first episode CNS-ID confirmed with magnetic resonance imaging (MRI) white matter changes (except in optic neuritis) were included. International Paediatric MS Study Group 2007 definitions were used for acute disseminated encephalomyelitis (ADEM), clinically isolated syndrome (CIS) and neuromyelitis-optica (NMO). All paediatricians, paediatric neurologists, and ophthalmologists were sent monthly cards (n=4095) through the British Paediatric and Ophthalmological Surveillance Units (BPSU and BOSU) from Sep 2009-Sep 2010. Clinicians completed a standard questionnaire and provided the MRI copy to be classified by neuroradiologists blinded to clinical features. An expert panel met quarterly to review notifications. Incidence rates were calculated using mid-2010 population estimates. Results: Card return rates were 94% BPSU and 78% BOSU. Information was available for 200/222 cases (90%) notified. After removal of duplicates and cases not fitting inclusion criteria, 125 cases (64 females, 101 white, median age 10.9 years) were included giving a minimum incidence of first onset CNS-ID in children aged 1-15 years old in the British Isles as 9.83 per million children per year (95% CI 8.18-11.71). Sex ratios varied significantly when evaluated as a function of age with more females in older age groups. Children with ADEM were significantly younger than CIS cases. Childhood CNS-ID disorders were classified as ADEM in 32%, CIS in 66%, and neuromyeltis optic (NMO) in 2%. There was one ADEM death. Of the CIS cases with gadolinium scans, 10/38 (26%) fulfilled McDonald 2010 MRI criteria for MS diagnosis. Children with ADEM had higher CSF white cell counts (p=0.005) and fewer CSF positive oligoclonal bands (p=0.011) compared to CIS. The majority (89%) received either intravenous corticosteroids (84%) and/or oral prednisolone. Conclusions: This population study establishes minimum incidence, clinical, MRI and investigative features of childhood CNS-IDs and of MS on the revised 2010 McDonald criteria at presentation in the British Isles.